KIỂM TRA ĐÁNH GIÁ Vì SỰ TIẾN Bộ CỦA NGƯỜI HỌC THÔNG QUA HOẠT ĐỘNG CHỮA CÁC CÂU HỎI MANG TÍNH PHÂN LOẠI TRONG NHỮNG BÀI KIỂM TRA THƯỜNG XUYÊN - Nguyễn, Thị Như Quỳnh (NHÀ XUẤT BẢN ĐẠI HỌC QUỐC GIA HÀ NỘI, 2019)
Nghiên cứu này tìm hiểu về thái độ của sinh viên năm thứ nhất hệ đào tạo cử nhân tài năng mới đối với hoạt động giáo viên chỉ tập trung chữa một số câu hỏi mang tính phân loại trong bài kiểm tra. Dữ liệu nghiên cứu là bảng hỏi, phỏng vấn bán cấu trúc với sinh viên và giáo viên đứng lớp, dự giờ, và ghi âm lời giảng của giáo viên. Kết quả nghiên cứu cho thấy thay đổi rõ rệt trong thái độ của học sinh và cách thức tiếp cận của giáo viên trong giờ chữa bài kiểm tra thường xuyên, dù rằng những chuyển biến về điểm số bài kiểm tra chưa thực sự rõ ràng. Điều này mở ra tiềm năng sử dụng những bài kiểm tra thường xuyên như một phần của hoạt động kiểm tra đánh giá vì sự tiến bộ của người học. Corrective feedback, especially its effectiveness is learners’ written and spoken production, receives constant discuss by practitioners as well as researchers such as Trustcot (e.g. 1996, 1999, 2007) and Ferris (e.g. 1999, 2002, 2003, 2004, 2006, 2010). Nevertheless, feedback on learners’ errors while doing grammatical practices seems to be out of question in the current trends of focusing on communicative competence or regarded as a simple technical solution in the 4.0 time. This study aims at providing students with specific information on their performance and guiding the teacher’s feedback by focusing only on the discrimination items through analysing the students’ answers to 20-50 questions in each of the 10 lesson-revision tests. The effectiveness of this practice was identified by comparing learners’ scores and analysing their answers to the questionnaires at the beginning and end of the treatment, their responses to the interviews at the end of the course, their attitudes in the class and the teacher’s audiorecorded instruction while checking these items. The results show some changes in the learners’ attitudes and the teacher’s instruction methods even though the learners’ scores did not increased as much as expected. This reveals the potential of using classroom tests as part of formative assessment which aims at improving not only learners’ performance but also the teacher’s instruction.